A Factor VIII Neutralizing Monoclonal Antibody and a Human Inhibitor Alloantibody Recognizing Epitopes in the C2 Domain Inhibit Factor VIII Binding to von Willebrand Factor and to Phosphatidylserine - Shima, Midori; Scandella, Dorothea; Yoshioka, Akira; Nakai, Hiroaki; Tanaka, Ichiro; Kamisue, Seiki; Terada, Shigeki; Fukui, Hiromu (Thrombosis and Haemostasis, 1993)
A neutralizing monoclonal antibody, NMC-VIII/5, recognizing the 72 kDa thrombin-proteolytic fragment of factor VIII light chain was obtained. Binding of the antibody to immobilized factor VIII (FVIII) was completely blocked by a light chain-specific human alloantibody, TK, which inhibits FVIII activity. Immunoblotting analysis with a panel of recombinant protein fragments of the C2 domain deleted from the amino-terminal or the carboxy-terminal ends demonstrated binding of NMC-VIII/5 to an epitope located between amino acid residues 2170 and 2327. On the other hand, the epitope of the inhibitor alloantibody, TK, was localized to 64 amino acid residues from 2248 to 2312 using the same recombinant fragments. NMC-VIII/5 and TK inhibited FVIII binding to immobilized von Willebrand factor (vWF). The IC50 of NMC-VIII/5 for the inhibition of binding to vWF was 0.23 μg/ml for IgG and 0.2 μg/ml for F(ab)'2. This concentration was 100-fold lower than that of a monoclonal antibody NMC-VIII/10 which recognizes the amino acid residues 1675 to 1684 within the amino-terminal portion of the light chain. The IC50 of TK was 11 μg/ml by IgG and 6.3 μg/ml by F(ab)'2. Furthermore, NMC-VIII/5 and TK also inhibited FVIII binding to immobilized phosphatidylserine. The IC50 for inhibition of phospholipid binding of NMC-VIII/5 and TK (anti-FVIII inhibitor titer of 300 Bethesda units/mg of IgG) was 10 μg/ml.